2022
DOI: 10.1155/2022/5603355
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Nano-Cutting Fluid in New Cutting and Forming Processes on Heat Transfer Performance of Mechanical Engineering

Abstract: In order to strengthen the thermal conductivity of green cutting fluid and the influence of nano-cutting fluid from new cutting and forming processes on heat transfer performance of mechanical engineering, a research method was proposed based on the influence of nano-cutting fluid from new cutting and forming processes on heat transfer performance of mechanical engineering. The dispersion stability, thermal conductivity, and viscosity characteristics of the nanofluid were studied, and the effects of acidificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In the paper [22], specifically, the chip removal procedures in the MQL system were constrained by the addition of hBN to the nanolubricant. In the paper [23], the stickiness was increased due to its inadequate cooling and its restricted ability to remove the chips generated, and in the study [24], a little diminution in tool life was seen when the concentration ratio reached 1.5 vol%.…”
Section: Introductionmentioning
confidence: 98%
“…In the paper [22], specifically, the chip removal procedures in the MQL system were constrained by the addition of hBN to the nanolubricant. In the paper [23], the stickiness was increased due to its inadequate cooling and its restricted ability to remove the chips generated, and in the study [24], a little diminution in tool life was seen when the concentration ratio reached 1.5 vol%.…”
Section: Introductionmentioning
confidence: 98%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%